2023
DOI: 10.7759/cureus.37086
|View full text |Cite
|
Sign up to set email alerts
|

Giant Adrenal Cyst: A Case Report

Abstract: Giant adrenal cysts are rare lesions, most often discovered incidentally. In this case report, a patient presenting with nonspecific abdominal distension is described. Imaging studies revealed a vast cystic mass closely attached to the left adrenal gland. Neither routine laboratory tests nor endocrine function tests revealed abnormalities. By performing open surgery, the cystic mass was completely removed. According to the pathological results, the wall of the cystic mass has an endothelial structure and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Another study reported a case of a 31×17×16 cm giant unilocular cystic lesion closely attached to the left adrenal gland [17]. Due to the huge volume and the risk of malignancy, they did an open excision and the final histopathology confirmed it as an angiomatous adrenal endothelial cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a case of a 31×17×16 cm giant unilocular cystic lesion closely attached to the left adrenal gland [17]. Due to the huge volume and the risk of malignancy, they did an open excision and the final histopathology confirmed it as an angiomatous adrenal endothelial cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Even if these patients recover well and have an uncomplicated postoperative period, repeat CT scans should be performed every six months for a minimum of 18 months 18 . For patients who are not surgical candidates, aspiration of the cyst may be a viable option instead of surgery 19 . In addition to surgery, decortication and marsupialization have also been considered as alternatives for treating big cysts, particularly those that are attached to many ISSN: 2250-1177 [6] CODEN (USA): JDDTAO organs and may be challenging to remove 19 .…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are not surgical candidates, aspiration of the cyst may be a viable option instead of surgery 19 . In addition to surgery, decortication and marsupialization have also been considered as alternatives for treating big cysts, particularly those that are attached to many ISSN: 2250-1177 [6] CODEN (USA): JDDTAO organs and may be challenging to remove 19 . Although absolute alcohol-based sclerosing therapy has also been reported, it is linked to a 30% to 50% high recurrence rate 20 .…”
Section: Discussionmentioning
confidence: 99%